Therapeutic Effects of Olive Oil in Diabetic Rat - Fahad, Omar Attalla (International Journal of Psychosocial Rehabilitation, 2020)
The current study conducted for evaluation the therapeutic effects on diabetic rats. Forty male rats were used in this study which divided into 4 groups, 10 rats were in each group, Group A serve as control group, Group B given alloxan monohydrate at dose of (150 mg/ kg), Group C given alloxan monohydrate at dose of (150 mg/ kg) then received orally (0.5 ml/kg B.W) of olive oil for 4 weeks, Group D received orally (0.5 ml/kg B.W) of olive oil for 4 weeks (control positive). blood samples were aspirated at zero, 15 and 30 days of experiment to estimate the blood glucose, cholesterol and HDL. Pancreas and liver were taken for histopathology. The results showed an increase in blood glucose, cholesterol in group B and decreasing in HDL levels. Group C showed significant (P